STUDY OF THE INVESTOR EXPECTATIONS WITH BLACK-LITTERMAN MODEL IN OPTIMAL PORTFOLIO SELECTION: AN APPLICATION ON ISTANBUL STOCK EXCHANGE CORPORATION - Seda SÜER (Fırat University, 2019)
The Black-Litterman Optimization Model, developed by Fischer Black and Robert Litterman, is an optimal portfolio construction model that the expectations of the investor can be brought in the formulation of optimization. Investors return expectations are a kind of estimated information, also referred to as personal or subjective returns. In the process of optimal portfolio selection Black-Litterman Model combine the subjective expectations of an investor regarding the expected returns of one or more assets with the market equilibrium vector of expected returns to compute the new mixed estimate of expected returns. Investors expected return vector (Q), represents the investor's estimated expected return on each asset in the portfolio. Black-Litterman Model with these expectations can be included in the optimization process and be reflected in the final return. In this study, optimal portfolio selection was performed by applying the Black-Litterman Model to National 100 Index of 39 companies showing the continuity for the period between 01 January 2004 to 30 June 2013 on Istanbul Stock Exchange Corporation (BIST). Then, by applying the Black-Litterman Model final returns are calculated and therefore the portfolio weights are revised. In addition, by investor expectations under 100% certainty rate new final returns are calculated and portfolio weights are revised accordingly, by applying the Black-Litterman Model without the variance matrix expectations. The purpose of this study is to calculate the investor's one single expectation and the certainty rate which is determined by the investor for this expectation and to implement a different analysis for the revision of the portfolio weight in the final return line. Consequently, with Black-Litterman Model portfolios with sensible portfolio weights are obtained by applying reverse optimization to the final returns.